Fenomena Gadget dan Perkembangan Sosial bagi Anak Usia Dini - Pangastuti, Ratna (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This paper seeks to explain the picture of the gadget phenomenon that develops in early childhood in some areas, analyze the impact of gadgets for early childhood social development, analyze the social development of early childhood gadget users. By using the method of document study, the author then collects various documents of research to be analyzed by meta synthesis to produce final conclusions. Of the nine documents that researchers collect randomly from various sources, then got the end result that the phenomenon of gadgets has penetrated the area in Indonesia both urban and rural areas and at an early age (Â± 1 year to 6 years) have known and used gadgets. The social impacts raised from the children of this gadget user show positive data, meaning that gadgets greatly affect the behavioral development and social interaction. The social development of children using gadgets even to addiction is mostly they look passive in the association with peers, they prefer to be alone and comfotr with their gadget, their motor activity was very minimal. So that the optimization of a childs self-potential is required the participation of parents, which becomes the most important element in the formation and development of the childs personality.